Decolorization of Orange G using Exiguobacterium spp. BAB 5584: A Sustainable Approach for Textile Dye Remediation - Singh, Vartika; singh, Jaswant; Chauhan, Abhishek; Shukla, Kartikeya (International Journal of Membrane Science and Technology, 2023)
The unregulated discharge of untreated effluents from textile industries poses a significant environmental threat to both aquatic and terrestrial ecosystems. In response, this study investigates the efficacy of a biological remediation approach employing an adapted native bacterial strain exhibiting superior decolorization capabilities compared to other isolated strains. The isolated bacterial strain, demonstrating remarkable decolorization potential, undergoes further optimization and identification processes. The native bacterial strain is identified as Exiguobacterium spp. BAB-5584 through 16S rRNA sequencing. This strain is subsequently employed for the degradation of Orange G azo dye under optimized conditions of pH, temperature, and dye concentration. The adapted bacterial strain showcases its maximum degradation efficiency, achieving a remarkable 98% degradation of Orange G at a concentration of 100mg/l with in a 24-hours incubation period at 370C and pH 7. Characterization of the degradation products is carried out using gas chromatography-mass spectrometry (GC-MS). To assess the ecological impact of the treated wastewater, germination assays are performed using chickpea and mung seeds. Notably, there is no observed inhibition of germination when compared to the control group, affirming the non-toxic nature of the degraded metabolites.